Integration of Civic Education in Climate Crisis and Natural Disaster Management in South Tangerang City - Nurdiyana; Sulastri; Suwandi; Putri, Riska (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The increasing urbanization and climate change in South Tangerang City have intensified the frequency and impact of natural disasters. Therefore, effective disaster mitigation strategies are essential to protect communities and reduce potential losses. This study examines the role of citizenship education (Pancasila and Civic Education - PPKn) in addressing climate crisis challenges and disaster preparedness. By integrating disaster risk reduction (DRR) into the PPKn curriculum, this research highlights the importance of equipping students with knowledge and skills to actively participate in disaster prevention and management efforts. The methodology employed is a literature review analyzing government reports, disaster data from the South Tangerang Regional Disaster Management Agency (BPBD), and related academic literature. The findings reveal that, despite various mitigation efforts by the local government, gaps remain in public awareness and active community participation in disaster preparedness. The PPKn curriculum, enriched with DRR materials, can play a crucial role in bridging these gaps by educating the younger generation about disaster resilience. This study emphasizes the need for collaboration among the government, educational institutions, and society to foster a strong culture of preparedness. Integrating disaster mitigation strategies into education not only strengthens community resilience but also aligns with national goals for disaster risk reduction. Reforming the PPKn curriculum can significantly contribute to enhancing the resilience of South Tangerang City residents in facing climate change challenges.